2016
DOI: 10.1002/ecs2.1578
|View full text |Cite
|
Sign up to set email alerts
|

Vacant lots as a habitat resource: nesting success and body condition of songbirds

Abstract: Abstract. Vacant lots are a common feature throughout many cities and may provide necessary habitat resources for urban bird populations. We evaluated the quality of vacant lots throughout Baltimore, Maryland, by determining how differences in vacant lot properties related to songbirds' nesting success and body condition. We observed 130 nests from American robins (Turdus migratorius), gray catbirds (Dumetella carolinensis), and northern cardinals (Cardinalis cardinalis) across the city and assessed body condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…, Pham et al. , Ernstson , Locke and Baine , Rega‐Brodsky and Nilon ). Many studies have shown that sociodemographic disparities, particularly differences in household wealth, are predictors of urban tree canopy (Schwarz et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…, Pham et al. , Ernstson , Locke and Baine , Rega‐Brodsky and Nilon ). Many studies have shown that sociodemographic disparities, particularly differences in household wealth, are predictors of urban tree canopy (Schwarz et al.…”
Section: Discussionmentioning
confidence: 98%
“…Interest in the socioecological dimensions of urban vegetation has been growing over the past decade, with much of the interest focusing on spatial patterns of urban tree canopies (Heynen 2003, Hope et al 2003, Martin et al 2004, Perkins et al 2004, Kinzig et al 2005, Heynen et al 2006, Grove et al 2009, Conway et al 2011, Pham et al 2012, Ernstson 2013, Locke and Baine 2014, Rega-Brodsky and Nilon 2016. Many studies have shown that sociodemographic disparities, particularly differences in household wealth, are predictors of urban tree canopy (Schwarz et al 2015).…”
Section: Social Determinants Of Land Abandonmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we found that trees were the most important feature for abundant native bird species [8], while areas of dense shrubs best supported successful nesting efforts of common songbird species [26]. Additional global studies highlight the importance of vegetation structure to increase bird species richness in a variety of urban greenspaces (e.g., [6,[56][57][58]).…”
Section: Discussionmentioning
confidence: 61%
“…Vacant lot locations were provided by the Baltimore City Office of Sustainability. Lots were located at least 250 apart from one another, as a part of a parallel vacant lot bird community study [8,26]. We visited sites during May-July of 2013-2015 to classify the site by its setting and vegetation origin, sample the vegetation community and structure, and collect data on the bird community.…”
Section: Site Selectionmentioning
confidence: 99%